Hiperrealitas Pembaca pada Utas Alternative Universe Boys Love Karakter Anime Chainsaw Man di X (Twitter) - Nikmah, Niken Nur Khilatun; Hidayat, Medhy Aginta (Journal of Urban Sociology, 2024)
This study aims to uncover the hyperreality conditions experienced by some readers when reading the alternative universe boys love threads of the Chainsaw Man anime characters of the X (Twitter) accounts @haezellatos and @devilsmete. The method used in this research is a qualitative method using a netnographic approach. In addition, the researchers used interviews, observations and documents to collect data. This research uses snowball sampling technique and triangulation of data sources as a technique to check the validity of the data. The results of this study indicate that the alternative universe boys love thread in the Chainsaw Man anime character X (Twitter) accounts @haezellatos and @devilsmete creates a hyperreality condition in readers. This is due to readers being unable to distinguish between the artificial reality, namely the alternative universe boys love thread of the Chainsaw Man anime character, and the original reality, namely the Chainsaw Man anime. Finally, what is experienced by the reader creates hyper-reality conditions and hyper-sensitivity conditions, where artificial reality and original reality merge into one, causing the reader to experience hyper-reality in the alternative universe boys love anime character Chainsaw Man thread.Keywords: alternative universe, anime, boys love, hyperreal, X (Twitter)